Context Jibas dalam Kualitas Pelayanan Akademik di MIN 2 Kota Kediri - Widada Hamid (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2023)
The purpose of this study is to evaluate the school institution's policy in implementing the JIBAS program. JIBAS is used to increase the degree of learning services at MIN 2 Kediri. In collecting field research data, researchers used data triangulation, namely interviews, documentation and observation. In the assessment, researchers use the CIPP model. The method in this research is a qualitative method of case study type. In qualitative research, the main sources of data are speech and action, while documents and other data are called complementary data. The data were then reviewed using three techniques, namely data compression, data presentation, conclusion drawing, and data validity checking. The results of this study show that the implementation of JIBAS in the quality of academic services is needed by school institutions with the aim of achieving more effective, instructive, fast and precise academic services in data presentation.